Highlight of severe acute respiratory syndrome coronavirus-2 vaccine development against COVID-19 pandemic. Issue 1 (31st December 2020) - Liu, Cheng-Hsuan; Huang, Hsuan-Yang; Tu, Yung-Fang; Lai, Wei-Yi; Wang, Chia-Lin; Sun, Jun-Ren; Chien, Yueh; Lin, Tzu-Wei; Lin, Yi-Ying; Chien, Chian-Shiu; Huang, Chih-Heng; Chen, Yuh-Min; et al.
Abstract : The pandemic caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has brought an unprecedented impact upon the global economy and public health. Although the SARS-CoV-2 virology has been gradually investigated, measures to combat this new threat in public health are still absent. To date, no certificated drug or vaccine has been developed for the treatment or prevention of coronavirus disease Extensive researches and international coordination has been conducted to rapidly develop novel vaccines against SARS-CoV-2 pandemic. Several major breakthroughs have been made through the identification of the genetic sequence and structural/non-structural proteins of SARS-CoV-2, which enabled the development of RNA-, DNA-based vaccines, subunit vaccines, and attenuated viral vaccines. In this review article, we present an overview of the recent advances of SARS-CoV-2 vaccines and the challenges that may be encountered in the development process, highlighting the advantages and disadvantages of these approaches that may help in effectively countering COVID-19.